MODEL ESTIMASI PENURUNAN MUKA TANAII(LAND IDENCE) WILAYAH DKI JAKARTA: BERDASARKAN DATA TINGGI DARI PENGUKURAN SIPAT DATAR - YULAIKHAH
Land subsidence phenomena in DKI Jakarta has occurred for along time. In order to reduce the financial loss that it causes, the haracteristics and patterns of the land subsidence in the Jakarta area should be known as early as possible by estimating the most suitable land subsidence model. This research tries to estimate land subsidence models of DKI Jakarta and then predicts the magnitude of it in the future. The models that are used are the geometric models : Polynomial Velocity Surface (PVS), Polynomial Acceleration Surface (PAS), and Combination Model (MK). The used data are the station height3 obtained from four leveling surveys conducted in 1982, 1991, 1997 and 1 999, respectively. For comparison, computation of land subsidence using the available geological model is carried out based on the borehole and the soil mechanic laboratory result at Tongkol street. The result shows that the geometric models (PVS, PAS and MK) can only generate the trend of land subsidence, and not the whole subsidence signal, and MK model give better results. The geological model give a more detail picture of land subsidence but it has no spatial variation. It is shown by the different results of land subsidence computed using both models, geometric and geological, at Tongkol street.